Wprowadzanie zmian organizacyjnych w kontekście przezwyciężania zjawisk kryzysowych organizacji - Bieńkowska, Agnieszka; Kral, Zygmunt; Zabłocka-Kluczka, Anna (Introducing organizational changes in context dealing with crisis occurrences of an organization, 2006)
A need of effectuating and differentiating organizational changes depending on character of crisis occurrences was justified. A classification of organizational changes in context of crisis occurrences was presented. A ways of reacting in crisis situation and crisis of an organization were characterized. The most important methods of introducing changes in crisis occurrences were pointed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 193-201